2016
DOI: 10.1186/s12970-016-0146-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of inhalation ofCitrus sinensisflowers andMentha spicataleave essential oils on lung function and exercise performance: a quasi-experimental uncontrolled before-and-after study

Abstract: BackgroundRecently, there has been an increased interest in the effects of essential oils on athletic performances and other physiological effects. This study aimed to assess the effects of Citrus sinensis flower and Mentha spicata leaves essential oils inhalation in two different groups of athlete male students on their exercise performance and lung function.MethodsTwenty physical education students volunteered to participate in the study. The subjects were randomly assigned into two groups: Mentha spicata an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 52 publications
1
31
0
Order By: Relevance
“…de Sousa et al, observed the spasmolytic activity of carvone and limonene, which can assist proper respiratory and cardiovascular functioning [18]. A recent human study demonstrated the beneficial effects of SEO on lung function and exercise performance [19], which may be at least X-axis denotes protein-based biomarker readouts. Y-axis denotes the relative expression levels of biomarkers compared with the vehicle control values in the log form.…”
Section: Bioactivity Profile Of Seo In the Human Dermal Fibroblast Symentioning
confidence: 99%
“…de Sousa et al, observed the spasmolytic activity of carvone and limonene, which can assist proper respiratory and cardiovascular functioning [18]. A recent human study demonstrated the beneficial effects of SEO on lung function and exercise performance [19], which may be at least X-axis denotes protein-based biomarker readouts. Y-axis denotes the relative expression levels of biomarkers compared with the vehicle control values in the log form.…”
Section: Bioactivity Profile Of Seo In the Human Dermal Fibroblast Symentioning
confidence: 99%
“…Essential oil (EO), as the main component used in inhalation therapy, has been widely investigated for its therapeutic effects. Evidence indicates that EOs can successfully reduce anxiety and relieve pain when combined with conventional treatment [ 1 , 2 ]. EOs can be administered through oral consumption, direct skin contact, or inhalation [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Essential oils (EOs) of the Mentha species, regarded as peppermint oil, was reported to ameliorate histamine and ovalbumin (OVA)-induced bronchial asthma [ 13 ]. Interestingly, healthy adults nebulized with Mentha EOs (MEO) for 5 min following 1500 m running tests showed significant improvement in lung function and exercise performance [ 14 ]. There is accumulating evidence regarding the use of essential oils against urban air pollution to reduce the risk of respiratory diseases [ 15 ].…”
Section: Introductionmentioning
confidence: 99%